Analisis Faktor - Faktor yang Mempengaruhi Financial Statement Fraud pada Perusahaan Bank Syariah Indonesia: Studi Kasus pada Perusahaan Bank Syariah yang Terdaftar pada Bursa Efek Indonesia Tahun 2021-2023 - Frichillia Elvira Agustina; Fatchan Achyani (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to determine the analysis of the analysis of factors that affect the financial statement fraud in the company of bank syariah indonesia quantitative research. The population that was the focus of this study was all Indonesian Islamic banks listed on the Indonesia Stock Exchange during the period 2021 to 2023. The selection of Islamic commercial banks as the subject of research is based on unique principles applied in its operations. Sampling technique using purposive sampling technique. The results of the study can be concluded that the financial targets, financial stability does not affect the financial statement fraud, external pressure affects the financial statement fraud.